1999
DOI: 10.1891/0889-8391.13.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Styles and Life Events in Subsyndromal Unipolar and Bipolar Disorders: Stability and Prospective Prediction of Depressive and Hypomanic Mood Swings

Abstract: We examined the interaction of cognitive styles and life events in predicting the depressive and hypomanic mood swings of 43 undergraduates meeting criteria for a subsyndromal mood disorder (i.e., cyclothymia, dysthymia, or hypomania) or no lifetime diagnosis. Participants completed symptom, cognitive style, and life events measures on three separate occasions as the different mood states characteristic of their subsyndromal disorder naturally occurred. Normal controls were assessed in three separate normal mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
148
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(161 citation statements)
references
References 0 publications
11
148
1
1
Order By: Relevance
“…For example, in combination with negative life stressors, bipolar individuals with dysfunctional attitudes or depressogenic attributional styles are more likely to develop affective symptoms (Alloy et al, 1999). These findings support the rationale for utilizing cognitive-behavioral interventions aimed at modifying maladaptive cognitive styles and decreasing the impact of environmental stress.…”
Section: Introductionsupporting
confidence: 52%
“…For example, in combination with negative life stressors, bipolar individuals with dysfunctional attitudes or depressogenic attributional styles are more likely to develop affective symptoms (Alloy et al, 1999). These findings support the rationale for utilizing cognitive-behavioral interventions aimed at modifying maladaptive cognitive styles and decreasing the impact of environmental stress.…”
Section: Introductionsupporting
confidence: 52%
“…The HMI (Alloy, Reilly-Harrington, Fresco, Whitehouse, & Zechmeister, 1999;Francis-Raniere et al, 2006) is a 28-item self-report inventory designed to measure the severity of current (hypo)manic symptoms and is administered and scored similarly to the BDI. The HMI assesses the presence and severity of affective, cognitive, motivational, and somatic symptoms of (hypo)mania.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Seligman et al (1988) found that self-blaming attributions for failure correlated with severity of depression in both unipolar and bipolar depression. Prospective studies have also shown that negative cognitive styles predict increases in bipolar depressive symptoms over time (Alloy, Reilly-Harrington, Fresco, Whitehouse, & Zechmeister, 1999;Johnson & Fingerhut, 2004). Thus it is important to acknowledge that a previous history of depression or current depressive symptoms may account for cognitive patterns observed among persons who also have a history of mania.…”
mentioning
confidence: 99%